2014
DOI: 10.1124/jpet.114.215913
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Intestinal Human Pregnane X Receptor Protects against Azoxymethane/Dextran Sulfate Sodium–Induced Colon Cancer

Abstract: The role of intestinal human pregnane X receptor (PXR) in colon cancer was determined through investigation of the chemopreventive role of rifaximin, a specific agonist of intestinal human PXR, toward azoxymethane (AOM)/dextran sulfate sodium (DSS)-induced colon cancer. Rifaximin treatment significantly decreased the number of colon tumors induced by AOM/DSS treatment in PXR-humanized mice, but not wild-type or Pxr-null mice. Additionally, rifaximin treatment markedly increased the survival rate of PXR-humaniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…Cheng et al (16) studied the anti-inflammatory effect of rifaximin in a colitis model and showed that rifaximin acted on human PXR and caused NF-κB inhibition. Another study demonstrated that rifaximin induced specific activation of PXR in PXR-humanized mice and mediated the inflammation, cancer cell proliferation and pro-apoptotic events in colon cancer (25). The results from the present study are in line with these reports and further show that rifaximin is a potent inhibitor of the release of angiogenic mediators.…”
Section: Discussionsupporting
confidence: 91%
“…Cheng et al (16) studied the anti-inflammatory effect of rifaximin in a colitis model and showed that rifaximin acted on human PXR and caused NF-κB inhibition. Another study demonstrated that rifaximin induced specific activation of PXR in PXR-humanized mice and mediated the inflammation, cancer cell proliferation and pro-apoptotic events in colon cancer (25). The results from the present study are in line with these reports and further show that rifaximin is a potent inhibitor of the release of angiogenic mediators.…”
Section: Discussionsupporting
confidence: 91%
“…PXR also inhibited HT29 xenograft tumor growth in mice as a result of cell cycle arrest at G0/G1 phase along with elevated p21 expression and inhibited E2F1 expression. A similar tumor suppressor role for PXR was observed in a very recent study of colon cancer (Cheng et al, 2014). Treatment with rifaximin, which selectively activates intestinal PXR, significantly decreased the number of colon tumors induced by azoxymethane (AOM)/dextran sulfate sodium (DSS) in PXR-humanized mice, but not in wild-type or PXR-null mice (Cheng et al, 2014).…”
Section: Differential Role Of Pxr In Cancersupporting
confidence: 81%
“…A similar tumor suppressor role for PXR was observed in a very recent study of colon cancer (Cheng et al, 2014). Treatment with rifaximin, which selectively activates intestinal PXR, significantly decreased the number of colon tumors induced by azoxymethane (AOM)/dextran sulfate sodium (DSS) in PXR-humanized mice, but not in wild-type or PXR-null mice (Cheng et al, 2014). Additionally, rifaximin treatment increased the survival rate of PXR-humanized mice compared to wild-type or PXR-null mice.…”
Section: Differential Role Of Pxr In Cancersupporting
confidence: 81%
“…Interestingly, this report also indicated that expression of PXR is reduced in human colon cancer tissues, albeit using a relatively small sample size (Ouyang et al, 2010). A tumor-suppressive role of PXR was further supported by another report where intestine-specific activation of PXR by rifaximin significantly reduced azoxymethane/dextran sulfate sodium-induced colon cancer in human PXR transgenic but not WT or PXR 2/2 mice, possibly through the PXR-NF-kB axis (Cheng et al, 2014).…”
Section: Downloaded Frommentioning
confidence: 58%